Identification of phenolic constituents and antioxidant activity of Aloe barbadensis flower extracts. Issue 1 (1st January 2018) - Debnath, Trishna; Ghosh, Mithun; Lee, Young Min; Nath, Narayan Chandra Deb; Lee, Kwang-Geun; Lim, Beong Ou
ABSTRACT: Aloe vera ( Aloe barbadensis Miller) has been used as topical and oral therapeutic. This research highlights the phenolic constituents' profile and antioxidant activity of 70% ethanol extracts of Aloe vera flower for the first time. The ethanol-based extracts showed the inhibition for linoleic acid oxidation and free radical-induced DNA damage. Among about 11 phenolic constituents of the extract, identified by using high performance liquid chromatography (HPLC), the content of vanillic acid was highest, corresponding to strong antioxidant activities of the extract. The extracts elevated superoxide dismutase, catalase, and glutathione peroxidase enzymes activities in the liver tissue of hydrogen peroxide-treated BALB/c mice. The radical-scavenging activities of the extracts were well-correlated to the total phenolic content. Therefore, Aloe bardadensis flower might be an effective source of natural antioxidant. GRAPHICAL ABSTRACT: UF0001